Malfunction of Subpectorally Implanted Cardiac Resynchronization Therapy Defibrillators Due to Weakened Header Bond. (6th November 2012) - HAYAT, SAJAD A; KOJODJOJO, PIPIN; MASON, ANTHONY; BENFIELD, ANN; WRIGHT, IAN; WHINNETT, ZACHARY; LIM, PHANG BOON; DAVIES, D. WYN; LEFROY, DAVID; PETERS, NICHOLAS S; KANAGARATNAM, PRAPA
<x xml:space="preserve">Abstract</x> Malfunction of Subpectorally Implanted Cardiac Resynchronization Therapy. Background: Implantable cardioverter defibrillator (ICD) implantation has increased significantly over the last 10 years. Concerns about the safety and reliability of ICD systems have been raised, with premature lead failure and battery malfunctions accounting for the majority of reported adverse events. We describe the unique mode of presentation, diagnosis, and management of cardiac resynchronization therapy defibrillators (CRT‐D) malfunctions that were caused by weakened bonding between the generator and header. Methods and Results: Between June 2008 and December 2009, 22 Teligen™ ICDs and 24 Cognis™ CRT‐Ds were implanted subpectorally at our institution, until a product advisory was issued. Of 24 Cognis™ CRT‐D implants, 3 patients presented with CRT‐D malfunctions. All our cases presented with initially intermittent and then persisting increases in shock lead impedance, associated with nonphysiological noise in the shock electrogram channels. These issues were rectified by generator change. Postexplant laboratory analysis confirmed inadequate bonding between device header and titanium casing in all cases, resulting in loosening and rocking of the header followed by fatigue‐induced fracture of the shock circuitry. Conclusion: Weakened bonding between the header and generator casing of subpectorally implanted CRT‐Ds can result in fractures and malfunction of the HV circuit. Physicians monitoring patients with devices affected by the product advisory should remain vigilant in order to diagnose and manage similar device malfunction expediently. (J Cardiovasc Electrophysiol, Vol. 24, pp. 351‐355, March 2013)